Kinetic-thermodynamic study of the oxidative stability of Arbequina olive oils flavored with lemon verbena essential oil - Cherif, Marwa (2021)
Arbequina extra-virgin olive oils were flavored with lemon verbena (Aloysia citrodora) essential oil (0.10.4%, w/w), being evaluated quality parameters (free acidity, peroxide value, UV-extinction coefficients), oxidative stability, antioxidant and total reducing capacity. The kinetic-thermodynamic nature of the lipid oxidation was evaluated by Rancimat (110150 °C). The essential oil addition promoted the antioxidant and total reducing capacities but, unfortunately, increased primary and secondary related quality parameters. Moreover, flavoring decreased the oils' oxidative stability. The kinetic-thermodynamic data showed that unflavored oils had significantly lower oxidation reaction rates (0.0550.06492 h1), more negative temperature coefficient (0.0268°C1), higher temperature acceleration factor (1.852), greater activation energy (82.7 kJ mol1) and frequency factor (10.9 × 109 h1), higher positive enthalpy of activation (79.4 kJmol-1), lower negative entropy of activation (131.8 J mol1K1) and greater positive Gibbs free energy of activation (129.95135.23 kJ mol1), showing that oils oxidation was negatively influenced by the essential oil incorporation. Overall, oxidation had a non-spontaneous, endothermic and endergonic nature. Finally, olive oils could be satisfactorily classified (principal component and linear discriminant analysis) according to the flavoring level, using quality-antioxidant-stability or kinetic-thermodynamic datasets. The latter showed a less predictive performance, although ensuring the full discrimination of unflavored from flavored oils.